Predictors of knowledge, attitude and perception of diphtheria infection and vaccination among medical students in Abubakar Tafawa Balewa University, Bauchi North-Eastern Nigeria - Musa, Abubakar; Abba, Usman; Oluwatobi, Esther Adesina; Ojochenemi, Aishat Haruna; Abutu, Abel Acheneje; Jibril, Muhammad Bashar; Abdullahi, Mohammed Kabir (International Journal Of Community Medicine And Public Health, 2025)
Background: Diphtheria is a highly contagious infection caused by Corynebacterium diphtheriae and other strains that affect respiratory system. Commonly transmitted through inhalation of airborne droplets or handling contaminated items. The main stay of prevention is vaccination. Hence, this study assessed the level of knowledge, attitude and perception of diphtheria infection and vaccination among medical students in Abubakar Tafawa Balewa University Bauchi State, Northeastern Nigeria. Methods: A cross-sectional descriptive study was carried out among 210 Medical students in Bauchi State from April to November, 2024. A stratified sampling technique, semi-structured self-administered questionnaire were used and the data was analyzed using SPSS version 23.0. Results: The mean age among the respondents was 21±3. The study reveals poor knowledge 60.5%, then 90.5% and 99% of respondents had positive attitude and perception towards diphtheria infection and vaccination respectively. Age, religion and level of study were found to be statistically associated with knowledge of diphtheria infection with p=0.001, p=0.001 and p=<0.001 respectively. Age, religion and level of study remained independent predictors of knowledge of diphtheria infection and vaccination. Conclusions: The knowledge of diphtheria infection and vaccination among the respondents was poor with positive attitude and perception. Age, religion and level of study were the factors associated with knowledge of diphtheria infection. Age, religion and level of study remained independent predictors of knowledge of diphtheria infection and vaccination. There is need to strengthen campaign for diphtheria vaccination targeting students to prevent them from the infection and its effects.